The Pengaruh Kompensasi, Motivasi, dan Lingkungan Kerja Terhadap Kinerja Karyawan PT Yamaha Indonesia (Studi Kasus Karyawan Departemen - Devi Sibagariang; Indra Juhana; Rizky Handoyo Putra; Sunita Dasman (Prosiding SEMANIS: Seminar Manajemen Bisnis, 2024)
PT Yamaha Indonesia, a musical instrument manufacturing company, aims to achieve profit through the production of Upright Pianos and Grand Pianos. Employees, as a vital factor, influence the company's performance. PT Yamaha Indonesia has 1500 employees and is capable of producing 40,000 piano units per year. Performance is measured by production output meeting targets, efficiency, and other factors. Research on the Painting Department of PT Yamaha Indonesia shows that compensation, motivation, and the work environment significantly influence employee performance. The T-test results indicate that compensation, motivation, and the work environment each have a significant impact. Simultaneously, these three factors have a 16.1% influence, while 83.9% is influenced by other variables outside the study. The coefficient of determination results in an Adjusted R Square value of 0.161, indicating that the influence of compensation, motivation, and the work environment on employee performance is 16.1%, with the remaining 83.9% influenced by other variables. The F-test results yield a p-value of 0.025, rejecting H0, indicating that the regression model is accurate in predicting the influence of compensation, motivation, and the work environment on employee performance in the Painting Department of PT Yamaha Indonesia. The T-test results for the Compensation variable are -0.748 with a p-value of 0.459 (greater than 0.05), so H0 is rejected, meaning that Compensation significantly influences employee performance. Similarly, the T-test results for the Motivation variable are -2.911 with a p-value of 0.006, and for the Work Environment variable, it is 2.713 with a p-value of 0.010, both rejecting H0 and indicating that Motivation and the Work Environment significantly influence employee performance. In conclusion, it can be inferred that compensation, motivation, and the work environment are crucial in enhancing the performance of employees in the Painting Department of PT Yamaha Indonesia.